ICTs usage and skills matching at work: some evidence from Spain - Caparrós-Ruiz, Antonio (Emerald, 2020)
This article focuses on the Spanish labour market, and its primary objectives are to analyse the factors determining the ICTs usage at workplace, and examine how the workers’ e-skills match with the job tasks requiring ICTs. Furthermore, it will explore whether doing ICTs training activities has a positive effect on the probability of carrying out appropriately the ICTs at work. The methodology applied is an ordered response model analysing how the workers’ e-skills match with the knowledge required to the ICTs usage at the job. This econometric specification will control by the selection bias generated because not all employees use ICTs to perform the job tasks. Data are obtained from the Survey on Equipment and Use of ICTs in Households (ICTS-H Survey). Educational attainment and the type of ICTs training are the most relevant variables to explain the ICTs usage and the quality of the job match. Data used are cross-sectional, and it excludes the possibility of observing how the workers’ careers evolve depending on their ICTs training. The methodology applied allows us to obtain the marginal effects to the variables explaining the probability of using ICTs at job, and how the workers’ knowledge match with the e-skill required by the employers. The results are a source of information to policymakers about how workers face the introduction of ICTs in the labour market. To the best of our knowledge, the article’s topic and its methodology are unprecedented in the economic literature and, specially, in the Spanish case.
This research is a post-print version of the article "ICTs usage and skills matching at work: some evidence from Spain" published by International Journal of Manpower (Vol. 42 No. 6, pp. 1064-1083).
Keywords: Mercado de trabajo - España; Training; ICTs; Job Matching; Ordered Models